Analisis Pemahaman Mahasiswa Program Studi Bahasa Mandarin dan Kebudayaan Tiongkok Universitas Al Azhar Indonesia terhadap Program Merdeka Belajar Kampus Merdeka - Feri Ansori; Tri Budianingsih (Universitas Al Azhar Indonesia, 2022)
The “Independent Campus, Freedom to Learn” (MBKM) Policy, which was initiated by the Minister of Education, Culture, Research and Technology is an innovative step to improve the quality of human resources to be ready to enter the world of work. This policy gives freedom to students to be able to carry out activities outside their department either at the same university in different department or at other universities or other institutions that collaborate in MBKM activities. This research was conducted using a field survey method, the research aspects including the student’s level of knowledge on the MBKM program, sources of information for the MBKM program, activities in the MBKM program, competency improvement through the MBKM program and others. The object of this research are the students of the Chinese Language and Culture department at the University of Al Azhar Indonesia, discussing the level of student understanding regarding the MBKM policies. The research found that most of the students did not get clear information about the MBKM program. Although all respondents stated that the MBKM program provided good benefits for improving competence and soft skills in preparing life after graduation, but at the implementation stage there were still several obstacles. The findings of the study also provided suggestions for improving the implementation of MBKM activities.Keywords - Competency improvement, MBKM policy, Student understanding